2020
DOI: 10.3389/fmed.2020.616957
|View full text |Cite
|
Sign up to set email alerts
|

Role of Complement and Histones in Sepsis

Abstract: The wide use of the mouse model of polymicrobial sepsis has provided important evidence for events occurring in infectious sepsis involving septic mice and septic humans. Nearly 100 clinical trials in humans with sepsis have been completed, yet there is no FDA-approved drug. Our studies of polymicrobial sepsis have highlighted the role of complement activation products (especially C5a anaphylatoxin and its receptors C5aR1 and C5aR2) in adverse effects of sepsis. During sepsis, the appearance of these complemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 67 publications
0
19
0
Order By: Relevance
“…Likewise, NETosis/ETosis, a regulated form of necrosis that is restricted to immune cells like neutrophils (NETosis) and other granulocytes or macrophages (ETosis), also contributes to the formation of CHs (20)(21)(22)(23)(24). In sepsis, the decondensed chromosome networks, termed as neutrophil extracellular traps (NETs), are mainly formed by neutrophil protrusions after stimulations of interleukin (IL)-8, lipopolysaccharide (LPS), TNF-a, complement, high hemodynamic forces and cold-inducible RNA-binding protein (11,(25)(26)(27)(28). Growing evidence have suggested that activation of TLR2/4 as well as complement play a significant role in initiating NETosis and mediating dysregulated innate immune response, forming a vicious cycle to cause subsequent tissue injury and organ dysfunction (29)(30)(31).…”
Section: Basics Of Circulating Histonesmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, NETosis/ETosis, a regulated form of necrosis that is restricted to immune cells like neutrophils (NETosis) and other granulocytes or macrophages (ETosis), also contributes to the formation of CHs (20)(21)(22)(23)(24). In sepsis, the decondensed chromosome networks, termed as neutrophil extracellular traps (NETs), are mainly formed by neutrophil protrusions after stimulations of interleukin (IL)-8, lipopolysaccharide (LPS), TNF-a, complement, high hemodynamic forces and cold-inducible RNA-binding protein (11,(25)(26)(27)(28). Growing evidence have suggested that activation of TLR2/4 as well as complement play a significant role in initiating NETosis and mediating dysregulated innate immune response, forming a vicious cycle to cause subsequent tissue injury and organ dysfunction (29)(30)(31).…”
Section: Basics Of Circulating Histonesmentioning
confidence: 99%
“…Sepsis is associated with the activation of all three complement pathways (classical, alternative and lectin), resulting in the appearance of proinflammatory anaphylatoxins C3a and C5a (28). Bosmann et al and Kalbitz et al collectively showed that the interaction between C5a and its receptor (C5aR1 and C5aR2) significantly contributed to the formation of extracellular histones that further mediated acute lung injury and cardiomyopathy in sepsis (29,44).…”
Section: Complement Activationmentioning
confidence: 99%
“…The immunosuppressed stage can last for many months or even years and comes with increased risk for death due to secondary infections. Many aspects of sepsis have been highlighted recently like the presence of exosomes [77], complement and histones [78], metabolic changes [79] and ROS and inflammasomes [80]. Gene expression analysis of sepsis patients revealed CXCL8, tumor protein P53 and TNF as particularly important based on a subsequent pathway analysis [81,82].…”
Section: The Erythrocyte In Sepsismentioning
confidence: 99%
“…The neutralization of C5a with antibodies or the absence of C5aR1 prevents the appearance of extracellular histones, cell death and organ failure in sepsis. Blocking C5a with antibodies can significantly improve the survival rate of septic mice (17); In addition to C5a, other complement components such as C3a, C4, FBP have many relevant studies in sepsis (14,18,19). Some scholars have found that when sepsis occurs, the complement system and neutrophils are activated by pathogens and endogenous danger signals at the same time.…”
Section: Introductionmentioning
confidence: 99%